POTENCIAL DE OBTENÇÃO DE AÇÚCARES FERMENTESCÍVEIS A PARTIR DO FARELO DE CANOLA EMPREGANDO-SE AS β-GLICOSIDASES PRODUZIDAS POR Penicillium glabrum - Martins, Eduardo Henrique (2019)
Cellulases, including β-glucosidases, are used in the production of second-generation bioethanol. Its production can occur from filamentous fungi, using a source of carbon (substrate) for its induction. In this sense, lignocellulosic biomass, such as bran, bagasse and straw, can be used as alternative substrates. Currently, the high costs of obtaining these enzymes make their use unfeasible. Thus, the optimization of the production process of the β-glucosidases from agroindustrial residues can reduce the costs of obtaining this biofuel. The present study had the objective of evaluating the potential of obtaining fermentable sugars from canola meal, using the β-glucosidases produced by Penicillium glabrum. Initially, the optimal conditions for the production of β-glucosidases by a Penicillium glabrum strain were established, using canola meal (Brassica campestris) as substrate. To this end, the Rotational Compound Central Design (DCCR) applicable to the Response Surface Methodology (RSM) was used. These same statistical tools were used in order to establish the best hydrolysis conditions of the chemically pretreated canola meal using the P. glabrum β-glucosidases produced under optimized conditions. As a result, the maximum level of β-glucosidases production was reached when the fungus was cultured at pH adjusted to 6.0, substrate concentration of 2% and culture time of 6.5 days, corresponding to 22.45 ± 1.04 U mL-1. Furthermore, the highest levels of fermentable sugars were obtained when the hydrolysis process was conducted at 65 °C, pH 4.0, for 75 hours, using an enzyme concentration corresponding to 13.75 U g-1. Under these optimized conditions, glucose levels corresponded to 34.54 mg g-1 substrate. By means of the results obtained, it can be concluded that canola meal is a promising raw material, both for the production of low-cost β-glucosidases and for obtaining fermentable sugars, aiming the production of bioethanol.